Air-Drying Llama Sperm Affects DNA Integrity - Carretero, María Ignacia; Chaves, María Graciela; Arraztoa, Claudia Cecilia; Fumuso, Fernanda Gabriela; Gambarotta, Mariana Carla; Neild, Deborah Margarita (Frontiers in Veterinary Science, 2020)
The objective of this study was to evaluate the effects of air-drying preservation on llama sperm DNA. Semen collections were carried out using electroejaculation under general anaesthesia. A total of 16 ejaculates were processed from 4 males (n = 4, r = 4). Each sample was diluted 4:1 in a collagenase solution in TALP media, then incubated and centrifuged at 800g for 8 min. The pellet was re-suspended to a concentration of 20 million sperm/ml in TALP. Then the samples were placed onto sterile slides forming lines and were left to dry under laminar flow for 15 minutes. After this, the slides were placed into Falcon centrifuge tubes and kept at 5 °C. Sperm characteristics (motility, membrane function, viability and morphology) were evaluated in raw semen and in the air-dried samples kept at 5 °C for 30 minutes. DNA evaluation (integrity and degree of chromatin condensation) was carried out in raw semen and in the air-dried samples after 30 minutes, 7, 14, 21, 30 and 60 days after preservation. To compare raw semen to the air-dried samples, a Wilcoxon test was used for all sperm characteristics except for DNA, where a paired Student t test was applied. A split plot design was used to compare chromatin condensation between the different periods of preservation and a Kruskal Wallis test was used to compare DNA integrity. Motility, membrane function, viability and sperm with intact DNA decreased in the air-dried samples (p < 0.05), while morphology and chromatin condensation were not affected (p > 0.05). No significant differences were observed in the percentage of sperm with condensed chromatin between the different periods of preservation (p > 0.05). On the other hand, a significant decrease in the percentage of sperm with intact DNA was observed as from day 7 of preservation (p < 0.05). In conclusion the air-drying process has a negative effect on llama sperm DNA, hence the media used will need to be improved to protect DNA and be able to implement this technique in this species.